Hadharah An-Nash, ‘Ilm Dan Falsafah Sebagai Metode Pengembangan Keilmuan Islam Di Era Kontemporer - Ida Wijayanti; Eva Dewi (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
Education is an important theme that cannot be separated from human life, because in principle the entire process of life is education. The view that education is very important has long been recognized by humans and it has been proven that education has given birth to civilizations that have been recorded in human history. Education is a conscious human effort in order to realize and shape the complete human person. Furthermore, education is a process of creating human persons who are useful for society, religion and the state. The issue of scientific dichotomy is an issue that never ends in Islamic education. According to Ahmad Barizi, there is a further mapping assumption between what is called revealed knowledge (knowledge that originates from God's revelation) and scientific knowledge (knowledge that originates and originates from the analysis of human thought) such as philosophy, social sciences, humanities sciences, natural sciences and exact sciences. An educational paradigm is needed that is able to direct the goals and objectives of Islamic education, especially Islamic scholarship in the contemporary era. In this paper the author will direct readers to the concept of how education referred to as hadhari education can become a way to develop Islamic scholarship in the contemporary or present era.